Modeling and Using Context 8th International and Interdisciplinary Conference, CONTEXT 2013, Annecy, France, October 28 - 31, 2013, Proceedings - Brézillon, Patrick; Blackburn, Patrick; Dapoigny, Richard (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the proceedings of the 8th International and Interdisciplinary Conference on Modeling and Using Context, CONTEXT 2013, held in Annecy, France, in October/November 2013. The 23 full papers and 9 short papers presented were carefully reviewed and selected from numerous submissions. In addition the book contains two keynote speeches and 9 poster papers. They cover cutting-edge results from the wide range of disciplines concerned with context, including: Cognitive Sciences (Linguistics, Psychology, Computer Science, Neuroscience), and computer science (artificial intelligence, logics, ubiquitous and pervasive computing, context-awareness systems), and the Social Sciences and Organizational Sciences, as well as the Humanities and all application areas, including Medicine and Law.